The impact of education on society in the novel Ahad by Zakaria Salleh - Mohd Hanafiah, Halis Azhan; Abdullah, Muhammad Alif Redzuan (Human Resources Management Academic Research Society (HRMARS), 2024)
This study was conducted with the aim of discussing the impact of education on society in the novel Ahad (1959) by Zakaria Salleh. The novel revolves around the lives of three identical twins named Amin, Hasan, and Dahalan during the time before, during, and after World War II. As educated characters, these three brothers play an important role in assisting their respective communities. The study outlines three objectives to be achieved. First, to identify the educational streams followed by the protagonists in the novel Ahad by Zakaria Salleh. Second, to describe the role of the protagonists in their respective communities in the novel Ahad by Zakaria Salleh. Third, to synthesize the relationship between education and the effectiveness of the protagonists' roles in their respective communities in the novel Ahad by Zakaria Salleh. This study utilizes the Sociology of Literature Theory proposed by Hippolyte Taine to achieve these three objectives. The findings of the study reveal that while in school, the character Amin received an English education, the character Hasan received a Malay education, and the character Dahalan received a religious education in a traditional religious school. The education received by the three of them enabled them to serve their communities in different fields, with Amin becoming a police officer, Hasan a modern farmer, and Dahalan a soldier/principal of a modern religious school. The study also found that with the education they received, the twin characters Amin, Hasan, and Dahalan were able to excel in their chosen professions and establish themselves as respected figures in their respective communities. The findings of this study suggest that the novel's portrayal aligns with the aspirations of the government and society in the 1950s, which sought to make education a tool for progress.